The Effect of Infant Massage Counseling on Infant Massage Practice by Mothers in Tugu Village, Jumantono Sub-District, Karanganyar Regency - Maecelina Hestin Ambasari; Sri Anggarini; Angesti Nugraheni (Journal of Health Science and Prevention, 2017)
Infant massage is a traditional child care whose efficacy has been proven. Therefore, the mothers need to get a health extension on the correct infant massage techniques so that they can do infant massage practice autonomously. This research aim to investigate the effect of infant massage extension on the infant massage practice by mothers in Tugu village, Jumantono sub-district, Karanganyar regency. The research used pre-experimental research method with the one group pretest-posttest design. Its samples consisted of 57 respondents and were taken by using proportional random sampling technique. The data of research were collected through checklist and analyzed by using the Wilcoxon test aided with the computer program of SPSS. Prior to the infant massage extension, the average score was 10.8, the highest score was 14, and the lowest score was 8. Following the extension, the average score was 25.6, the highest score was 29, and the lowest score was 21 as indicated by the score of Wilcoxon test in which the score of ZÃ‚ was -6.583 and the significance value was p = 0.000. Infant massage extension had an effect on the infant massage practice by mothers.